Proximity with the Other: A Multidimensional Et hi c of Responsibi l i t y i n Levi nas - T. J. Abraham (Asian Horizons, 2009)
Roger Burggraeve, Proximity with the Other: A Multidimensional Et hi c of Responsibi l i t y i n Levi nas, Bangalore: Dharmaram Publications, 2009, pages: vi + 152, ISBN: 978-81-89958-26-7.